Salvation and Morality: the Interconnections in African Thought - Ahortor, Godson (European Scientific Journal, ESJ, 2016)
A careful study and analysis of the religio-cultural practices of most tribal groups in Africa reveal that there is usually interconnectedness between the notions of salvation, morality and the conceptualisation of evil. It is thus believed that the ethical values and moral practices of such societies are sustained mainly by this interconnectedness of the concepts of the afterlife, morality and evil. As such, salvation among Africans in general can be said to have been greatly influenced by the ethical value systems of indigenous African societies from the perspective of their conceptualisation of evil. An investigation into the worldviews of the Tongu Mafi people reveals that this interconnectedness is firmly grounded in the beliefs and practices of the people. I contend in this paper therefore that the core indigenous beliefs, worldviews and practices of Africans are resilient and capable of sustaining their soteriological and moral practices. This paper is based on a phenomenological study of the Tongu Mafi people of Ghana mainly through interviews and observation of their religio-cultural practices. It concludes that the intersections of notions of salvation, morality and evil are couched in two moral principles: living a good life and avoiding evil. These two moral principles must be observed simultaneously in life for they constitute the foundations of the soteriological concerns and moral praxis of the Tongu Mafi people.